Utilizing Self Assessment in Improving Students’ Speaking Skill at spoken English for Survival English Class: English - Saiful Anwar (JOEY: Journal of English Ibrahimy, 2024)
An essential part of teaching evaluation. In this case, the evaluation done by students themselves. They did self-assessment. As the definition, it really worked for raising students speaking skill that linked to their performance to express some words in English. Goals for this study to disclose their concern in speaking skill through self-assessment such as their responsibility, autonomous, confidence as well as their competence. Many researchers approved that this strategy was good for increasing students’ skill in speaking. Classroom Action Research was the method for this study. Syah stated (2016) has to do with the teacher examining and delving deeper into concepts, problems, riddles, and challenges in their own classroom. The four stages for conducting the study were planning, action, observation and reflection. The participants of this research are English department students at University of 17 August 1945. Here, there are 32 students. In collecting data, based on the objectives, this study employs observation and questionnaire. The result shown that it genuinely gives impact the students speaking skills. Most of them have positive felling by utilizing this self-assessment in raising students speaking skills. This data can be seen from their responses. Thus, this strategy can be used in training students to be aware to their strength and weakness, to be autonomous learners and responsible to their works.